Forming and analysis of requirements to information-analytical system of management by safety of labour in enterprise - Евланов, Максим Викторович; Сердюк, Наталья Николаевна (Technology audit and production reserves, 2015)
The article examines the features of formation and analysis of functional requirements for the information and analytical system of safety management in the enterprise. We consider testing the previously developed technology accelerated the design of information systems. This subject of research due to the need to reduce the time required to perform the work on the formation and analysis of system requirements. The proposed organization of work allows formalizing and partially automated. The possibility of using the technology accelerated the design of information systems for the implementation of the formation and analysis of system requirements. This technology makes it possible to unify the work on the creation and processing of functional requirements. These results confirm the universality of the methods used with functional requirements. It shows a description of the method of allocating requirements of a mathematical model of a functional problem. Results of development of data schemes and of information and analytical system can be re-used to create similar systems for other companies.